PELAKSANAAN PEMBELAJARAN TEMATIK BAGI ANAK TUNAGRAHITA - Rahmi Yulianti (Universitas Negeri Padang, 2012)
Basic understanding of low-grade teachers in special schools Asih Padang Discourse on thematic learning is still limited. Implementation of the thematic learning for children of low base class Tunagrahita in SLB Discourse Asih Padang is still not optimal, yet according to the pattern of thematic learning. The results obtained from studies that not all teachers fully carrying out thematic learning., So suggestions that may be recommended are: 1) principals greater control over their learning process and to involve teachers in a seminar or training in order to better understand the thematic learning, 2) teachers should be more creative in implement the thematic learning. 3) the school must complete the facilities and infrastructure.